2015
DOI: 10.1080/21552851.2014.946935
|View full text |Cite
|
Sign up to set email alerts
|

Documenting, monetising and taxing Brazilian slaves in the eighteenth and nineteenth centuries

Abstract: Although Brazil imported more African slaves than any other country in the Americas, knowledge of the accounting and taxation of slave-related transactions in Brazil is under-developed. Here we explore Portuguese language documents showing how accounting and taxation were implicated in maintaining slavery in Brazil in the eighteenth and nineteenth centuries. We present examples of key documents involving slaves (such as inventory lists, rental agreements, insurance policies, and receipts) and explain how slave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
10
0
5
Order By: Relevance
“…Studies of accounting and slavery in Brazil are scarce. Analyses of 4 Brazilian documents relating to accounting and taxation practices have concluded that such practices were calculative recording and revenue raising mechanisms to facilitate the operation of Brazil's slave-based society (Rodrigues, Craig, Schmidt, & Santos, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of accounting and slavery in Brazil are scarce. Analyses of 4 Brazilian documents relating to accounting and taxation practices have concluded that such practices were calculative recording and revenue raising mechanisms to facilitate the operation of Brazil's slave-based society (Rodrigues, Craig, Schmidt, & Santos, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In cases of non-compliance concerning transactions involving slaves, a monetary fine equal to the market value of the slave was payablehalf to the informant and the other half to the Royal Crown (Berute, 2006;Rodrigues et al, 2015). Accounting devices helped to support slavery-related transactions.…”
Section: ---------------------------------Figure 2 About Here -------mentioning
confidence: 99%
See 2 more Smart Citations
“…Other forms of detailed agricultural accounting could also be found elsewhere in Europe, for instance in some regions of Spain, where seed banks known as "pósitos", regulated by the royal administration from the sixteenth century, issued loans to farmers and kept precise records of the ensuing credit relationships (Prado-Lorenzo, García-Salinero and González-Bravo 2017). Colonial plantations were another institutional setting that shaped the development of detailed forms of agricultural accounting, in particular for the valuation and oppression of slave populations treated as livestock (Barney 1994;Fleischman and Tyson 2004;Tyson 2004, 2011;Oldroyd, Fleischman and Tyson 2008;Rodrigues et al 2015;Rosenthal 2013aRosenthal , 2013bRosenthal , 2016Oldroyd 2004, 2005).…”
Section: Capitalismmentioning
confidence: 99%